Investigating the influence of generative ai integration within Problem Based Learning on students' critical thinking in introductory physics courses - Putu Prima Juniartina; Ni Luh Putu Mery Marlinda; I Made Oka Riawan; Kadek Dwi Hendratma Gunawan (Momentum: Physics Education Journal, 2026)
While the proliferation of Generative Artificial Intelligence (GenAI) offers transformative potential in higher education, its specific impact on critical thinking when integrated into structured pedagogical frameworks remains underexplored. This study investigates the integration of GenAI as a cognitive scaffold within a Problem-Based Learning (PBL) framework and its effect on the critical thinking skills of undergraduate students in an Introductory Physics course. Employing a quantitative quasi-experimental approach with a nonequivalent pretest-posttest control group design, the research involved 38 Science Education students. Participants were divided into an experimental group utilizing GenAI-assisted PBL and a control group receiving conventional instruction. Data were collected using 15 essay items assessing critical thinking based on Ennis’s taxonomy and analyzed via ANOVA and Normalized Gain (N-Gain). Results revealed a statistically significant difference (F=100.07; p<0.001), with the experimental group achieving a "Medium" gain (N-Gain = 0.477) compared to the control group's "Low" gain (N-Gain = 0.189). These findings address a critical gap by demonstrating that when GenAI is explicitly paired with the evaluative demands of PBL, it functions effectively as intelligent scaffolding rather than causing cognitive offloading, underscoring the necessity of embedding AI literacy into the modern science curriculum.